PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEBSITE APPSGEYSERS TEMA LINGKUNGAN SAHABAT KITA KELAS V SD MUHAMMADIYAH 2 FULL DAY EDUCATION SANGATTA UTARA - Agus Sultonik; Muhammad Siddik; Sudarman Sudarman (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
This research aims to determine the effectiveness and feasibility of using Appsgeysers Media website against the enhancement of student learning motivation. This research was done in SD Muhammadiyah 2 Full Day education North Sangatta because the teaching and learning activities conducted in the school especially in thematic lessons have used multimethods and multimedia, only still limited to the use of Microsoft Power point Medi so still impressed less effective. This type of research uses research and development methods or commonly called research and development. Samples use Lee and Owens development design methods. While the samples are taken in the class V (five) students, by using the pattern of one group Pretes and postest design. The Data used is a daily replay value before and after treatment, and then analyzed using test t. The results showed that interactive learning media based on website Appsgeysers used has a high level of effectiveness and feasibility. The high interest and motivation to learn that is high in the students ' interest also in teaching and learning activities. These findings are supported by the fact of the field where the average daily replay value of students increased 13.59% from 69.96 to 82.90.